Ethno-STEM Integration and Differentiated Learning for SDG 4 Quality Education: A Bibliometric Analysis and Systematic Review - Rosdiana; Ida Sriyanti; Ismet; Hamdi Akhsan; Effendi (Postgraduate, University of Mataram, 2026)
This study examines the integration of Ethno-STEM with differentiated learning through bibliometric analysis (15 Scopus documents, 2015–2024) and systematic literature review (15 articles, 2015–2024). Bibliometric results reveal a focused research landscape dominated by United States institutions, with steady publication growth post-2020. SLR synthesis identifies key pedagogical themes, including culturally responsive pedagogy, personalized learning, and the necessity of culturally adaptive teaching. The integration of these approaches fosters inclusive, student-centered environments that value local wisdom. However, challenges persist in teachers' culturally responsive STEM literacy and the design of diverse learning products. This research contributes to the development of the Differentiated Ethno-STEM Knowledge (DESK) framework, providing a systematic roadmap for teacher professional development. Conclusively, these findings offer actionable insights for sustainable education policy, directly advancing Sustainable Development Goal 4 (Quality Education) through contextually relevant and inclusive 21st-century learning strategies.